Protease XIV abolishes NHE inhibition by empagliflozin in cardiac cells - Chen, Sha; Schumacher, Cees A.; Van Amersfoorth, Shirley C. M.; Fiolet, Jan W. T.; Baartscheer, Antonius; Veldkamp, Marieke W.; Coronel, Ruben; Zuurbier, Coert J. (Frontiers in Physiology, 2023)
Background: SGLT2i directly inhibit the cardiac sodium-hydrogen exchanger-1 (NHE1) in isolated ventricular cardiomyocytes (CMs). However, other studies with SGLT2i have yielded conflicting results. This may be explained by methodological factors including cell isolation techniques, cell types and ambient pH. In this study, we tested whether the use of protease XIV (PXIV) may abrogate inhibition of SGLT2i on cardiac NHE1 activity in isolated rabbit CMs or rat cardiomyoblast cells (H9c2), in a pH dependent manner.Methods: Rabbit ventricular CMs were enzymatically isolated from Langendorff-perfused hearts during a 30-min perfusion period followed by a 25-minute after-dissociation period, using a collagenase mixture without or with a low dose PXIV (0.009 mg/ml) present for different periods.Empagliflozin (EMPA) inhibition on NHE activity was then assessed at pH of 7.0, 7.2 and 7.4. In addition, effects of 10 minutes PXIV treatment were also evaluated in H9c2 cells for EMPA and cariporide NHE inhibition.Results: EMPA reduced NHE activity in rabbit CMs that were not exposed to PXIV treatment or undergoing a 35-minutes PXIV treatment, independent of pH levels. However, when exposure time to PXIV was extended to 55 minutes, NHE inhibition by Empa was completely abolished at all three pH levels. In H9c2 cells, NHE inhibition by EMPA was evident in non-treated cells but lost after 10-minutes incubation with PXIV. NHE inhibition by cariporide was unaffected by PXIV.The use of protease XIV in cardiac cell isolation procedures obliterates the inhibitory effects of SGLT2i on NHE1 activity in isolated cardiac cells, independent of pH.